Incomplete cisplatin regimens in chemoradiation and its effect on outcomes for locally advanced cervical cancer. Issue 12 (6th October 2022) - Kotha, Nikhil V; Williamson, Casey W; Marra, Kyle V; McHale, Michael; Mell, Loren K; Mayadev, Jyoti S
Abstract : Objective: To identify factors associated with receipt of incomplete cisplatin during chemoradiation for locally advanced cervical cancer and its impact on outcomes. Methods: Patients with locally advanced cervical cancer treated with chemoradiation at our institution between November 2015 and August 2020 were retrospectively identified. Patients who received ≤4 cycles were identified as the 'incomplete' cohort and those who received 5–6 cycles as the 'complete' cohort. The primary endpoint of incomplete chemotherapy was evaluated with multivariable logistic regression. Secondary endpoints of locoregional failure, overall survival, and distant failure were evaluated in multivariable Cox and Fine–Gray models. Results: Of 140 patients with locally advanced cervical cancer that underwent chemoradiation, 22 (15.7%) received an incomplete cisplatin regimen (8 with 0 cycles, 14 with 1–4 cycles). The most common reasons for receiving incomplete treatment were comorbidities/infections (41%), unmet laboratory parameters (27%), and cisplatin intolerance (14%). In multivariable models, only poor (2–4) Eastern Cooperative Oncology Group performance status was a significant predictor as these patients were 41 times more likely to receive incomplete chemotherapy (odds ratio (OR), 95% confidence interval (CI) 4.57 to 375.15, p<0.001). Median follow-up time was 20 months (range 4–64). In multivariable models, receipt of incomplete cisplatin was significantly associated with higher recurrence (locoregional failure hazard ratio (HR) 3.02, 95% CI 1.08 to 8.45, p=0.03; distant failure HR 2.71, 95% CI 1.13 to 6.47, p=0.02) and worse survival (overall survival HR 4.91, 95% CI 1.27 to 18.98, p=0.02). Conclusion: Incomplete cisplatin regimen was associated with worse oncologic outcomes. Poor performance status was the only factor associated with receiving an incomplete regimen. This notable proportion of patients may be a target for better tolerated novel targeted anticancer agents in order to improve outcomes.